PLANNED LEARNING SITUATIONS IN PRESCHOOL - СТЕПИЋ, Гордана М. (Metodička teorija i praksa, 2026)
Planned learning, as defined within the current preschool education framework, differs significantly from its conceptualization in previous frameworks. This study aims to examine how preschool teachers provide support in planned learning situations and to what extent such practices are aligned with the current curriculum. The research employed a descriptive methodology, using content analysis of pedagogical documentation as the main technique and a protocol for pedagogical documentation analysis as the primary instrument. The sample comprised 50 thematic/project-based stories, which were analyzed to identify and categorize forms of educator support. Findings indicate that while most support strategies are generally consistent with the curriculum, their frequency and type vary. Teachers predominantly apply approaches that were common in earlier frameworks, whereas strategies specifically reflecting the current concept are less frequently observed. These results underscore the importance of teachers understanding the conceptual distinctions between planned learning across different frameworks and adopting pedagogical strategies that fully align with the current educational approach.